ANALISIS PENERAPAN KURIKULUM MERDEKA BELAJAR DI SMA NEGERI SEKOTA PADANGSIDIMPUAN - Hasrida Hutabarat; Muhammad Syahril Harahap; Rahmatika Elindra (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This study aims to determine the application of the independent learning curriculum at SMA Negeri in Padangsidimpuan city. This research was conducted from SMA N 1, to SMA N 8 Padangsidimpuan. This research used descriptive qualitative research method. Informants from this study were the vice principal of the curriculum, 3 teachers, and 3 students from each school. Data collection techniques used in this study were observation, questionnaires, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing or verification. Based on the results of research conducted at SMA Negeri Sekota Padangsidimpuan, from the results of the questionnaire filled out by 28 informants, it was obtained an average of 84.1071 with the category "already implemented". This is also reinforced by the results of interviews obtained by researchers from 28 teachers and 24 students who said that the independent learning curriculum had been implemented at SMA Negeri Sekota Padangsidimpuan according to the regulations from the Ministry of Education and Culture, although the results were not 100%. The implementation of the school assessment has also been carried out, namely the exam is held by the school, and the school has the freedom to determine the assessment. The implementation of a minimum competency assessment and a character survey have also been carried out, which is followed by class XI students whose names are registered at the center. Making RPP effective, efficient, and student-oriented learning has also been implemented, namely the teacher is free to choose, make, use, and develop the RPP format according to the situation and conditions. Admission of new students through zoning has also been implemented at SMA Negeri Sekota Padangsidimpuan, namely by following the rules from the Ministry of Education and Culture. Keywords: Independent Learning Curriculum